Medieval literature. vol.1. Pt.1, Chaucer and the alliterative tradition : with an anthology of medieval poems and drama - Ford, Boris (Harmondsworth : Penguin, 1982)
Previous ed. published: 1954. General Introduction / Boris Ford -- The social context of medieval english literature / Derek Brewer -- Asurvey of Medieval verse and Drama / John Speirs -- Postscripts -- Changing Perspectives / Derek Pearsall -- Middle english prose / T.P. Dolan and V.J. Scattergood -- The language of english medieval literature / Derek Brewer -- An anthology of medieval poems and drama -- Edited by thorlacturville-petre -- William Langland -- Apologia -- The harrowing of hell / From Piers Plowman -- Compiled / by Barry windeatt.
Keywords: ENGLISH LITERATURE - HISTORY AND CRITICISM; GOTHIC FICTION